Experimental oral transmission of chronic wasting disease to sika deer (Cervus nippon). Issue 1 (1st January 2020) - Sohn, Hyun-Joo; Mitchell, Gordon; Lee, Yoon Hee; Kim, Hyo Jin; Park, Kyung-Je; Staskevicus, Antanas; Walther, Ines; Soutyrine, Andrei; Balachandran, Aru
ABSTRACT: Chronic wasting disease (CWD) affects a broad array of cervid species and continues to be detected in an expanding geographic range. Initially introduced into the Republic of Korea through the importation of CWD-infected elk ( Cervus canadensis ), additional cases of CWD were subsequently detected in farmed Korean elk and sika deer ( Cervus nippon ). Wild and farmed sika deer are found in many regions of Asia, North America, and Europe, although natural transmission to this species has not been detected outside of the Republic of Korea. In this study, the oral transmission of CWD to sika deer was investigated using material from CWD-affected elk. Pathological prion (PrP CWD ) immunoreactivity was detected in oropharyngeal lymphoid tissues of one sika deer at 3.9 months post-inoculation (mpi) and was more widely distributed in a second sika deer examined at 10.9 mpi. The remaining four sika deer progressed to clinical disease between 21 and 24 mpi. Analysis of PrP CWD tissue distribution in clinical sika deer revealed widespread deposition in central and peripheral nervous systems, lymphoreticular tissues, and the gastrointestinal tract. Prion protein gene ( PRNP ) sequences of these sika deer were identical and consistent with those reported in natural sika deer populations. These findings demonstrate the efficient oral transmission of CWD from elk to sika deer.